This is an ongoing riddle to see how far we can get as a group.

Similar to “Just One” we try and figure out how to use six 6’s to equal 1 (O.K. that’s been solved) then 2, then 3, then 4, etc. to see how far we can get.

We are to come up with answers in sequence (2, 3, 4, 5, etc.) and the same person is not allowed to produce two answers in a row. So if I come up with the solution for 2. I must wait until someone else posts a solution for six 6’s equaling 3 before I provide a solution for six sixes equaling 7. Etc.

How high can we get 6 sixes to go?

Thank you Brent for your great submission.

We will keep this one unsolved until the great computer tells us there is no greater answer, yet 42 is the answer to everything.

Warning: Use of undefined constant bfa_comments - assumed 'bfa_comments' (this will throw an Error in a future version of PHP) in/home/customer/www/riddledude.com/public_html/wp-content/themes/atahualpa/comments.phpon line132Hey DK, sorry about duplicating the answer for 26. Hopefully you’ve gotten us back on track!

(66 + 66) / 6 + 6 = 28

(6-(6/6))*6-6/6=29

6 x ( 6 – 6/6) + 6 – 6 = 30

(6 + 6 + 6) / .6 + 6/6 = 31

(6*6)-6 + (6+6)/6 = 32

6×6 – ((6+6+6)/6) = 33

6 x 6 – 6/6 – 6/6 = 34

(6*6)-6/6+6-6=35

6+6+6+6+6+6=36

(6 x 6) + (66 / 66) = 37

I see that on April 15, Jack provided this solution:

6×6+6/6+6/6 = 38

(6(6)+ 6(6))/6(6)= 2

Well, I’m coming dangerously close to having a conversation with myself, but accepting Jack’s solution for 38, I have:

6 x 6 + (6 + 6 + 6)/6 = 39

((6+6+6+6)/6)/.6=40

sad I had to use the .6 :(

AH, Wait a minute that is wrong…

((6+6)/6 x (6+6))/.6=40

(6 + 6 + 6 + 6 + .6) / .6 = 41

I’m eager to see the solution “to everything” – 42 ?

sqrt(36)+6*6-6+6=42

Luca’s solution can be re-written using only 6’s as:

sqrt(6*6)+6*6-6+6=42

then

sqrt(6*6) + 6*6 * 6/6 = 43

Oops. Yeah i see, i accidentally put in 36 instead of 6*6.

Typo – mine should have read:

sqrt(6*6) + 6*6 + 6/6 = 43

(6*6)+6+(6+6)/6=44

Oh, this is one of my favourites!

666/6 – 66 = 45

6×6+6/.6+6-6=46

6×6 + 6 + 6 – 6/6 = 47

6*6+6+6+6-6 =48

(6 x (6 – 6/6) – .6) / .6 = 49

(6+6+6+6+6)/.6 = 50

(6 x (6 – 6/6) + .6) / .6 = 51

6/.6 + 6 * (6+6/6) = 52

66 – 6 – 6 – 6/6 = 53

6 x (6+ (6+6)/6)) + 6 = 54

(66 x 6 – 66) / 6 = 55

6×6 +6/.6+6/.6 = 56

Thanks for keeping this riddle alive Frank. One day we’ll hit the six 6’s wall!!

66 – 6/.6 + 6/6 = 57

6*6/.6 – (6+6)/6=58

6/6 x (6 x 6 – .6) / .6 = 59

6/.6 x 6 + (6-6)*6=60

6 / .6 x (6 x 6 + .6) / 6 = 61

(6/.6) x 6 + (6+6)/6 = 62

((6+6)/6)^6 – 6/6 = 63

(6/.6)*(6+6/6)-6=64

66 – 66 / 66 = 65

66+66-66=66

easy peasy

6/.6 x 6 + 6 + 6/6 = 67

66 +6/6+6/6 = 68

66 + (6 + 6 + 6) / 6 = 69 What an excellent adventure in math!

66 + 6 – (6+6)/6 = 70

(6 + 6) x 6 – 6 ^ (6 – 6) = 71

Where “^” represents “to the power of” and 6 raised to the power of 0 = 1.

6! / (6/.6) + (6-6)x6 = 72 where 6! is 6 factorial = 720

If factorial is not allowed then:

6 * (6+6) + (6-6)x6 = 72

:)